Regulation of CD137 expression through K‐Ras signaling in pancreatic cancer cells - Glorieux, Christophe; Huang, Peng (Cancer communications (London, England), 2019)
Background The interaction between CD137 and its ligand (CD137L) plays a major role in the regulation of immune functions and affects cancer immunotherapy. CD137 is a cell surface protein mainly located on activated T cells, and its regulation and functions in immune cells are well established. However, the expression of CD137 and its regulation in cancer cells remain poorly understood. The main purposes of this study were to examine the expression of CD137 in pancreatic cancer cells and to investigate its underlying mechanisms. Methods Cells containing inducible K‐RasG12V expression vector or with different K‐Ras mutational statuses were used as in vitro models to examine the regulation of CD137 expression by K‐Ras. Various molecular assays were employed to explore the regulatory mechanisms. Tumor specimens from 15 pancreatic cancer patients and serum samples from 10 patients and 10 healthy donors were used to test if the expression of CD137 could be validated in clinical samples. Results We found that the CD137 protein was expressed on the cell surface in pancreatic cancer tissues and cancer cell lines. Enzyme‐linked immunosorbent assay revealed no difference in the levels of secreted CD137 in the sera of patients and healthy donors. By using the K‐Ras inducible cell system, we further showed that oncogenic K‐Ras up‐regulated CD137 through the activation of MAPK (mitogen‐activated protein kinases) and NF‐κB (nuclear factor kappa‐light‐chain‐enhancer of activated B cells) pathways, as evidenced by significantly reduced CD137 mRNA expression led by genetic silencing of MAPK1 and p65, the key proteins involved in the respective pathways. Furthermore, we also found that the NF‐κB pathway was mainly stimulated by the K‐Ras‐induced secretion of interleukin‐1α (IL‐1α) which promoted the transcription of the CD137 gene in pancreatic cancer cell lines. Analysis of the TCGA (the cancer genome atlas) database also revealed a significant correlation between IL‐1α and CD137 expression (r = 0.274) in tumor samples from pancreatic cancer patients (P < 0.001). Conclusions The present study has demonstrated that the CD137 protein was expressed on pancreatic cancer cell surface, and has identified a novel mechanism by which K‐Ras regulates CD137 in pancreatic cancer cells through MAPK and NF‐κB pathways stimulated by IL‐1α.